The Dynamic Nexus Among Energy Consumption, Economic Growth, and Green Finance on Environmental Quality - Rahmayani, Dwi; Anas, Muhammad; Rachman, Mohammad Aulia; Vikia, Yahya Mahda (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2025)
This study investigates the relationship among energy consumption, economic growth, and green finance on environmental degradation. The Panel Dynamic ARDL-PMG was used to analyze the model in 33 provinces in Indonesia from 2010 to 2022. The result shows that GRDP per capita, Motor Vehicle Volume, and Green Finance significantly positively affect the Environmental Quality Index in the long run. In the short run, GRDP per capita significantly negatively affects the EQI. The findings of this study emphasize that the implementation of Indonesia's energy transition policy must be completed, including a comprehensive transition from upstream to downstream. The transition to a non-fossil fuel energy system must begin by converting fossil fuel power plants to non-fossil fuel power plants. Meanwhile, the government must expand public transportation and encourage electric vehicles through fiscal incentive schemes.